Pengaruh Citra Merek, Variasi Produk dan Gaya Hidup Terhadap Keputusan Pembelian Lipstik Wardah - Tati Susanti; Dewi Noor Susanti (P4M STIE Putra Bangsa, 2021)
This study aims to examine and analyze how the influence of brand image, product variation and lifestyle on Wardah lipstick purchasing decisions. Data was collected by distributing questionnaires. By using purposive sampling method, this study took a sample of 103 respondents to consumers who use Wardah lipstick in Kebumen Regency. The analysis used is validity test, reliability test, classical assumption test, multiple linear regression analysis test, hypothesis test and coefficient of determination. The analysis technique used is the SPSS 23.00 for windows analysis program. The results of this study indicate that brand image has a significant effect on purchasing decisions, product variations have a significant effect on purchasing decisions, lifestyle has a significant effect on purchasing decisions.